Paralogues of nuclear ribosomal genes conceal phylogenetic signals within the invasive Asian fish tapeworm lineage: evidence from next generation sequencing data. Issue 9 (August 2016) - Brabec, Jan; Kuchta, Roman; Scholz, Tomáš; Littlewood, D. Timothy J.
Graphical abstract: Highlights: Complete mitochondrial genomes and nuclear rRNA operons of Schyzocotyle acheilognathi were characterised and annotated. Genetic variation and phylogenetic relationships of 8 globally distributed Asian fish tapeworm populations were assessed. Nuclear rRNA operon paralogues were detected in all populations, having serious consequences for previous genetic studies. A broadly applicable sequencing approach using the Illumina MiSeq platform was successfully utilised. Abstract: Complete mitochondrial genomes and nuclear rRNA operons of eight geographically distinct isolates of the Asian fish tapeworm Schyzocotyle acheilognathi (syn. Bothriocephalus acheilognathi ), representing the parasite's global diversity spanning four continents, were fully characterised using an Illumina sequencing platform. This cestode species represents an extreme example of a highly invasive, globally distributed pathogen of veterinary importance with exceptionally low host specificity unseen elsewhere within the parasitic flatworms. In addition to eight specimens of S . acheilognathi, we fully characterised its closest known relative and the only congeneric species, Schyzocotyle nayarensis, from cyprinids in the Indian subcontinent. Since previous nucleotide sequence data on the Asian fish tapeworm were restricted to a single molecular locus of questionable phylogenetic utility—the nuclear rRNA genes-separating internal transcribed spacers—the mitogenomic data presented here offer a unique opportunity to gain the first detailed insights into both the intraspecific phylogenetic relationships and population genetic structure of the parasite, providing key baseline information for future research in the field. Additionally, we identify a previously unnoticed source of error and demonstrate the limited utility of the nuclear rRNA sequences, including the internal transcribed spacers that has likely misled most of the previous molecular phylogenetic and population genetic estimates on the Asian fish tapeworm.